OVERVIEW OF PATIENT SATISFACTION IN POST-OPERATING SERVICES AT THE CENTRAL GENERAL HOSPITAL (RSUP) PROF.DR.I.G.N.G. NGOERAH - Kurniyanta, I Putu; Senapathi, Tjokorda Gde Agung; Narakusuma, I Putu Fajar (E-Jurnal Medika Udayana; Vol 14 No 01 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i1.P08, 2025)
Background: Patient satisfaction is a response of health service users to the suitability between the level of importance and expectations before receiving health services and after receiving health services. Patient satisfaction with anesthesia services plays an important role in improving the quality of services and pain management of anesthesia. The quality of anesthesia services in hospitals and patient satisfaction can be measured through the assessment of effective doctor-patient communication and the assessment of postoperative pain intensity. Methods: This study is a descriptive cross-sectional study involving 184 respondents. Sampling was carried out using the consecutive sampling method on all postoperative patients at Prof.DR.I.G.N.G.Ngoerah General Hospital from May 2022 to June 2022. Data were obtained using the Iowa Satisfaction with Anesthesia Scale (ISAS) questionnaire, an effective doctor-patient relationship questionnaire to assess effective doctor-patient communication, and a Numeric Rating Scale (NRS) questionnaire. A descriptive analysis was carried out on demographic data, patient satisfaction with anesthesia services, effective doctor-patient communication and postoperative pain intensity. Results: The characteristics of respondents in this study include the gender of male respondents as many as 80 people (43.4%) and female as many as 104 people (56.5%). In this study, the largest category of respondents were female patients aged 36-55 years as many as 66 people, then successively followed by men aged 36-55 years as many as 30 people. Most of the respondents who participated in this study gave a good assessment and were satisfied with the performance of anesthesia and surgery at Prof.DR.I.G.N.G.Ngoerah Hospital, with a level of satisfaction with the anesthesia received of 94.6%. As many as 46.3% of respondents did not complain of postoperative pain, and as many as 51.1% of respondents complained of mild postoperative pain. The remaining 2.7% complained of moderate postoperative pain. Conclusion: Based on the results of the research that has been conducted, it can be concluded that the number of respondents who were satisfied with the anesthesia care received at Prof.DR.I.G.N.G.Ngoerah Hospital was 94.6%. As many as 88.6% of respondents considered doctor-patient communication in general at Prof.DR.I.G.N.G.Ngoerah General Hospital to be quite good. 46.3% of respondents did not complain of postoperative pain, and as many as 51.1% of respondents complained of mild postoperative pain. The remaining 2.7% complained of moderate postoperative pain.